Advances in design, simulation and manufacturing IV Proceedings of the 4th international conference on Design, Simulation, Manufacturing: the Innovation Exchange, DSMIE-2021, June 8–11, 2021, Lviv, Ukraine – Volume 1: Manufacturing and Materials Engineering - Ivanov, Vitalii; Trojanowska, Justyna; Pavlenko, Ivan; Zajac, Jozef; Peraković, Dragan (Switzerland Springer, 2021)
This book reports on topics at the interface between manufacturing and materials engineering, with a special emphasis on product design and advanced manufacturing processes, intelligent solutions for Industry 4.0, covers topics in ICT for engineering education, describes the numerical simulation and experimental studies of milling, honing, burnishing, grinding, boring, and turning, as well as the development and implementation of advanced materials. Based on the 4th International Conference on Design, Simulation, Manufacturing: The Innovation Exchange (DSMIE-2021), held on June 8-11, 2021, in Lviv, Ukraine, this first volume of a 2-volume set provides academics and professionals with extensive information on trends, technologies, challenges and practice-oriented experience in the above-mentioned areas.
Electronic reproduction
Keywords: Manufactures; Materials; Computer-aided engineering; Machines, Tools, Processes; Materials Engineering; Computer-Aided Engineering (CAD, CAE) and Design; Electronic books